2021
DOI: 10.2174/1573399816666200705210006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antidiabetic Drugs on Muscle Mass in Type 2 Diabetes Mellitus

Abstract: Background: When considering the administration of glucagon-like peptide-1 receptor agonists (GLP-1RAs), sodium-glucose cotransporter-2 (SGLT2) inhibitors, or metformin, it is important to understand their weight loss effect as well as the degree of muscle loss caused by each drug in clinical practice. Objective: To comparatively examine the effects of GLP-1RAs and oral antidiabetic drugs, including SG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…However, if sustained, caloric restriction will lead to variable weight loss depending on the partitioning of these calories between lean mass and fat mass. In medical practice, most diets and current pharmacotherapies will lead to some degree of lean mass loss (Figure 2) (6)(7)(8).…”
Section: Role Of Energy E Xpend Iture and Fat Oxidati On In Body Wei ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, if sustained, caloric restriction will lead to variable weight loss depending on the partitioning of these calories between lean mass and fat mass. In medical practice, most diets and current pharmacotherapies will lead to some degree of lean mass loss (Figure 2) (6)(7)(8).…”
Section: Role Of Energy E Xpend Iture and Fat Oxidati On In Body Wei ...mentioning
confidence: 99%
“…In large part, the reduction in energy expenditure induced by weight loss is attributable to the decline in lean mass, the metabolically active tissues (26‐28). Even if lifestyle modifications and currently available therapies for weight loss can deliver substantial decreases in fat mass, 15% to 40% of the weight loss represents reductions in lean mass (6‐8) (Figure 2). Resting energy expenditure is reduced by approximately 13 kcal/d for each kilogram of muscle mass lost, in contrast with the much lower 4.5‐kcal/d reduction for each kilogram of fat mass lost (29).…”
Section: Challenges Of Weight Loss and Its Maintenance With Emphasis ...mentioning
confidence: 99%
“…Guanidine was found to be the active ingredient of French lilac and in the 1950s metformin and phenformin, the two main biguanides, were introduced as a treatment for diabetes. Today metformin is prescribed to almost 120 million people for the treatment of type II diabetes (Ida et al, 2020). Interestingly, retrospective studies have shown that metformin is associated with a decreased cancer risk in diabetic patients (DeCensi et al, 2010).…”
mentioning
confidence: 99%
“…However, in another study involving 21 T2DM patients undergoing haemodialysis, addition of dulaglutide to insulin therapy significantly decreased FM and SMM, suggesting the sarcopenia risk of this drug 63 . A recent meta‐analysis of randomized controlled trials also indicated that semaglutide was associated with both weight loss and FFM decrease, prompting the need to understand drug‐specific effects on sarcopenic parameters 64 …”
Section: Effects Of Anti‐diabetic Drugs On the Musclementioning
confidence: 99%
“… 63 A recent meta‐analysis of randomized controlled trials also indicated that semaglutide was associated with both weight loss and FFM decrease, prompting the need to understand drug‐specific effects on sarcopenic parameters. 64 …”
Section: Effects Of Anti‐diabetic Drugs On the Musclementioning
confidence: 99%